2009
DOI: 10.1093/bja/aep300
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of individual patient data from clinical trials: epidural morphine for postoperative pain

Abstract: Analysis of individual patient data from high-quality clinical trials provides important insights into characteristics of new agents not immediately apparent from original trials, and also informing clinical practice. Prophylactic epidural morphine provides a better patient experience than IVPCA alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 24 publications
(9 reference statements)
2
53
0
3
Order By: Relevance
“…Pain is measured using standard scales, usually a visual analogue scale (0 to 100), a numeric rating scale (0 to 10), or a verbal rating scale (none, mild, moderate, severe). People whose postoperative pain is below 30/100 (or 3/10, or none or mild) tend to rate their experience as very good or excellent, whereas people with higher levels of postoperative pain tend to be more dissatisfied ( Mhuircheartaigh 2009). This accords with people's attitudes more generally .…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…Pain is measured using standard scales, usually a visual analogue scale (0 to 100), a numeric rating scale (0 to 10), or a verbal rating scale (none, mild, moderate, severe). People whose postoperative pain is below 30/100 (or 3/10, or none or mild) tend to rate their experience as very good or excellent, whereas people with higher levels of postoperative pain tend to be more dissatisfied ( Mhuircheartaigh 2009). This accords with people's attitudes more generally .…”
Section: Description Of the Conditionmentioning
confidence: 99%
“…Prophylactic analgesia with EREM leads to a more satisfactory patient experience than IV PCA. In this review [16], there were three strong findings. Epidural morphine resulted in greater patient satisfaction, despite higher rates of adverse events.…”
Section: Current Clinical Use Of Epidural Opioidsmentioning
confidence: 80%
“…It can be administered as a bolus (30-100 μg/kg) or as continuous infusion (0.2-0.4 mg/h), which seems to induce better quality analgesia, and alone or together with local anesthetics, as synergy between the drugs increases the overall analgesic effect [11,14]. In addition, controlled studies [15,16] have demonstrated that a single-dose EREM (Extended Released Epidural Morphine) can provide up to 48 hours very good quality of postoperative analgesia with an acceptable and predictable side effect profile (dose < 15 mg). Prophylactic analgesia with EREM leads to a more satisfactory patient experience than IV PCA.…”
Section: Current Clinical Use Of Epidural Opioidsmentioning
confidence: 99%
“…3 Intravenous analgesia was inferior to neuraxial analgesia. Extended-release epidural morphine resulted in a small therapeutic gain.…”
Section: Commentmentioning
confidence: 99%